Liposome-mediated CFTR gene transfer to the nasal epithelium of patients with cystic fibrosis - Caplen, Natasha J.; Alton, Eric W.F.W.; Mddleton, Peter G.; Dorin, Julia R.; Stevenson, Barbara J.; Gao, Xiang; Durham, Stephen R.; Jeffery, Peter K.; Hodson, Margaret E.; Coutelle, Charles; Huang, Leaf; Porteous, David J.; et al. (Nature medicine, 1995)
We report the results of a double-blind, placebo-controlled trial in nine cystic fibrosis (CF) subjects receiving cationic liposome complexed with a complementary DNA encoding the CF transmembrane conductance regulator (CFTR), and six CF subjects receiving only liposome to the nasal epithelium. No adverse clinical effects were seen and nasal biopsies showed no histological or immuno-histological changes. A partial restoration of the deficit between CF and non-CF subjects of 20% was seen for the response to low Cl− perfusion following CFTR cDNA administration. This was maximal around day three and had reverted to pretreatment values by day seven. In some cases the response to low Cl− was within the range for non-CF subjects. Plasmid DNA and transgene-derived RNA were detected in the majority of treated subjects. Although these data are encouraging, it is likely that transfection efficiency and the duration of expression will need to be increased for therapeutic benefit.